The impact of PICCO monitoring on traumatic shock: a systematic review and meta-analysis - Lin, Aihua; Lin, Zhangyue; Xu, Ke; Chen, Jiali; Ni, Xun (Frontiers in Medicine, 2025)
PurposeThis study aims to provide a systematic review and meta-analysis of Pulse Indicator Continuous Cardiac Output (PICCO) compared with conventional central venous pressure (CVP) monitoring in the treatment of traumatic shock.MethodsA systematic literature retrieval was conducted in databases including PubMed, Web of Science, Cochrane Library, Embase, and China National Knowledge Infrastructure (CNKI) from database inception to October 22, 2024. Keywords such as “PICCO,” “traumatic shock,” and “hemorrhagic shock” were used. Retrieved studies were screened according to pre-determined inclusion and exclusion criteria. The methodological quality and risk of bias were assessed using the Newcastle-Ottawa Scale (NOS) for cohort studies and the Cochrane “risk of bias” tool for randomized controlled trials (RCTs). Outcomes, including mortality, duration of mechanical ventilation, and length of ICU stay, were extracted and meta-analyzed.ResultsA total of 15 studies comprising 1,188 patients were included, with 597 monitored by PICCO and 591 by routine CVP. The risk of bias was assessed as low for all studies. PICCO-monitored patients showed a significantly shorter duration of mechanical ventilation compared to the control group [SMD in random effects model: −1.66; 95% CI: (−2.38, −0.94)]. However, no significant differences were found in mortality or length of ICU stay.ConclusionPICCO monitoring can improve the prognosis of traumatic shock patients by shortening the duration of mechanical ventilation, but it does not significantly affect mortality or length of ICU stay. Given the limitations of the included studies, further exploration is warranted to verify these conclusions.